2015
DOI: 10.1176/appi.ajp.2014.14070889
|View full text |Cite
|
Sign up to set email alerts
|

Citalopram, Methylphenidate, or Their Combination in Geriatric Depression: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Objective We evaluated the potential of methylphenidate to improve antidepressant response to citalopram in elderly depressed patients with respect to clinical and cognitive outcomes. Methods We conducted a 16-week randomized double-blind placebo-controlled trial for geriatric depression in 143 older outpatients diagnosed with major depression comparing treatment response in three groups: 1) methylphenidate and placebo (N=48); 2) citalopram and placebo (N=48); 3) methylphenidate and citalopram (N=47). Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 42 publications
(36 reference statements)
2
111
3
1
Order By: Relevance
“…Although the comorbidity between ADHD and depression is common, the evidence from clinical trials of ADHD medication (e.g., stimulants) are as yet too limited to warrant their use as treatment adjuncts for depression in selected patient groups (30). A recent clinical trial reported that the addition of methylphenidate to citalopram demonstrated an enhanced clinical response profile in mood and well-being, as well as a higher rate of remission, in older patients (31). Whether such effect would extend to other age groups warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the comorbidity between ADHD and depression is common, the evidence from clinical trials of ADHD medication (e.g., stimulants) are as yet too limited to warrant their use as treatment adjuncts for depression in selected patient groups (30). A recent clinical trial reported that the addition of methylphenidate to citalopram demonstrated an enhanced clinical response profile in mood and well-being, as well as a higher rate of remission, in older patients (31). Whether such effect would extend to other age groups warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent RCT, methylphenidate was added to the treatment with citalopram in 143 older people with depression [91]. Dosages of citalopram varied between 20-60mg/day, and of methylphenidate between 5-40 mg/day.…”
Section: Methylphenidate Treatment In Depression and Dementiamentioning
confidence: 99%
“…These medications are generally well tolerated, although proscribed in people with certain heart diseases, uncontrolled hypertension or a history of drug abuse. The drugs are increasingly used by geriatric psychiatrists to enhance mood for elderly patients with depression [54] and are useful for reducing daytime somnolence, both of which might be helpful for PD patients with fatigue.…”
Section: Fatiguementioning
confidence: 99%